National Art Library Catalogue / Victoria & Albert Museum - Victoria and Albert Museum - Library (2003)
[Dt.:] Online-Katalog der bedeutenden Referenzbibliothek des Victoria & Albert Museums London. - [Engl.:] Online catalogue of the important reference library at the Victoria & Albert Museum London.